ANALYSIS OF FACTORS AFFECTING LABOR ABSORPTION IN INDUSTRIAL SECTORS IN DISTRICT / CITY IN CENTRAL JAVA PROVINCE - Ovy Meilina Tyas Savitri; Sukardi; Heris Kencana TJ (FEB UNWIKU PURWOKERTO, 2019)
This research is entitled: